2017
DOI: 10.1159/000463393
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis in the Elderly and Impact of Institutionalization in the United States Renal Data System

Abstract: Background: We hypothesized that in the very elderly dialysis patients in the United States, institutionalization in nursing homes would increase mortality in addition to age alone. Methods: Incident dialysis patients from 2001 to 2008 above the age of 70 were included. Patients above 70 were categorized into 4 groups according to age as 70-75, 76-80, 81-85, and >85 years and further divided into institutionalized and noninstitutionalized. Kaplan-Meier survival curves were plotted to assess patient survival. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, in a study included 349,440 patients aged 70 years and over at the time of initiation of dialysis, institutionalized individuals had higher mortality as compared to non-instutionalized counterparts in the same age group. The researchers concluded that for frail elderly with advanced CKD, especially those with multiple comorbidities, or major neurocognitive disorders, conservative management with palliative or end-of-life care should be considered due to lack of therapeutic benefits of dialysis therapy [128]. Other studies have also observed that patients in nursing home or higher severity of frailty at dialysis initiation are associated with a substantial, post-dialysis decline in functional status and patient survival, respectively [129,130].…”
Section: Decision On Dialysis Initiationmentioning
confidence: 99%
“…For example, in a study included 349,440 patients aged 70 years and over at the time of initiation of dialysis, institutionalized individuals had higher mortality as compared to non-instutionalized counterparts in the same age group. The researchers concluded that for frail elderly with advanced CKD, especially those with multiple comorbidities, or major neurocognitive disorders, conservative management with palliative or end-of-life care should be considered due to lack of therapeutic benefits of dialysis therapy [128]. Other studies have also observed that patients in nursing home or higher severity of frailty at dialysis initiation are associated with a substantial, post-dialysis decline in functional status and patient survival, respectively [129,130].…”
Section: Decision On Dialysis Initiationmentioning
confidence: 99%